Outdoors Agricultural Insecticides Pose Worth Global Risks and Espousal of Safety Practices Among Farmers - Sarwar, Muhammad (International Journal For Research In Agricultural And Food Science, 2016)
This article summarizes the outcome of the peer review of the risks on the active substances and the representative formulations evaluated on the basis of the representative uses of insecticides. A toxic insecticide is any substance or mixture of substances intended for preventing, destroying or controlling any insect pest, including vectors of human or animal disease in or on their bodies, as well unwanted species of insects causing harm or otherwise interfering with the production, processing, storage, transport, or marketing of food, agricultural commodities, wood, wood products or animal feedstuffs. Next to these intended effects, insecticides may also have adverse health effects for human beings. The main adverse health effects are difficulty in breathing, headaches, neurological or psychological effects, irritation of skin and mucous membranes, skin disorders, effects on the immune system, cancer, and reproductive effects. The manifestation of these effects depends on the type of insecticide, toxicity level and duration of exposure. Researchers have also examined studies involving outdoor pesticides, such as insecticides, herbicides and fungicides, but the results are much less consistent. There has been a statistically significant association between outdoor exposure to herbicides and all types of childhood cancer combined, as well as childhood leukemia specifically. Insecticides have the solution to control insect problems, so, use of granular insecticides baits and a good granule spreader can ensure accurate and even applications throughout the entirely affected area. For reducing insecticide exposures, try to get rid of insect pests without chemicals, if using insecticides follow the safety directions, do not buy more insecticides than needed, and store or dispose of insecticides properly. Someone should not dispose of insecticides in the garbage and never pour poisons down the drain or sewerage. Prior to purchase, read and make sure to understand and follow the label directions as it contains important information on ingredients, precautions, security equipment, first aid, environmental hazards, use directions, storage and disposal. Also, it is dangerous and illegal; to not follow the directions on the label and be sure that the product can be used on the pest to which farmers want to manage and in the place want to use it. Overall, the consumption of low-fiber, fat-rich and calorie-rich diets, along with the use of alcohol, pose a much, much greater threat to human health than chemical residues in our food.